2008
DOI: 10.1155/2008/587239
|View full text |Cite
|
Sign up to set email alerts
|

False Memories of Emotional and Neutral Words

Abstract: Abstract. This study used the Deese-Roediger-McDermott paradigm [34] to investigate the direction and the extent to which emotional valence in semantic word lists influences the formation of false memories (FM). The experimental paradigm consisted of 1) a study phase (learning of neutral and negative lists of words semantically associated to a non-presented critical lure (CL), 2) a free recall phase, and 3) a recognition phase. Participants had to indicate whether the displayed item was "new" (new item or non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…Research that has teased apart the effects of negative and positive emotion on memory has revealed that negative emotion in particular is more likely to enhance the vividness of a memory (e.g., Mickley & Kensinger, 2009) and to increase the likelihood of endorsing an item (e.g., Budson et al, 2006; Dougal & Rotello, 2007; Sharkawy et al, 2008). Sometimes this effect of negative emotion seems to result from an influence on a person’s willingness to attribute an event to their past (Brainerd, Stein, Silveira, Rohenkohl, & Reyna, 2008; Dougal & Rotello, 2007), reflecting an influence on response bias rather than on memory accuracy.…”
Section: Emotional Content and The Retention Of Autobiographical Mmentioning
confidence: 99%
“…Research that has teased apart the effects of negative and positive emotion on memory has revealed that negative emotion in particular is more likely to enhance the vividness of a memory (e.g., Mickley & Kensinger, 2009) and to increase the likelihood of endorsing an item (e.g., Budson et al, 2006; Dougal & Rotello, 2007; Sharkawy et al, 2008). Sometimes this effect of negative emotion seems to result from an influence on a person’s willingness to attribute an event to their past (Brainerd, Stein, Silveira, Rohenkohl, & Reyna, 2008; Dougal & Rotello, 2007), reflecting an influence on response bias rather than on memory accuracy.…”
Section: Emotional Content and The Retention Of Autobiographical Mmentioning
confidence: 99%
“…Research has indicated an increase in overall memory performance for information with positive or negative emotional valence (Adelmann & Estes, 2013; Kensinger & Corkin, 2003). Furthermore, emotionality of word lists has also been found to increase false recognition in DRM tests (Howe, Candel, Otgaar, Malone, & Wimmer, 2010; Sharkawy, Groth, Vetter, Beraldi, & Fast, 2008), however possible differences arise between lists of negative and positive valence, with an increase in false recognition of negative word lists, and a decrease in false recognition of positive lists, relative to lists rated as neutral (Brainerd, Stein, Silveira, Rohenkohl & Reyna, 2008). The effect of emotionality on false recall is less clear.…”
mentioning
confidence: 99%
“…Previous research has shown that a DRM effect can be observed when list items are associates of emotional critical lures, though the direction of the effect varies between studies. Some studies have shown that emotional DRM lists produce lower levels of false memory than neutral lists (e.g., Kensinger & Corkin, 2004;Palmer & Dodson, 2009;Pesta, Murphy, & Sanders, 2001), whereas others have shown that emotional lists lead to higher levels of false memory (e.g., Brainerd, Stein, Silveira, Rohenkohl, & Reyna, 2008;Dewhurst et al, 2012;El Sharkawy, Groth, Vetter, Beraldi, & Fast, 2008). These differences are likely due to the use of different lists (see Dewhurst et al for further discussion of this).…”
mentioning
confidence: 99%